Prevalence of Cumulative Trauma Disorders within Office Workers in Palestine - Farah Melhem; Hiba Shahin; Mahmoud Abu Kishek; Shireen Debits (My University, 2015)
Cumulative trauma disorders are considered as occupational diseases affect business owners in a bad manner. They mainly occur due to performing repetitive actions for a long period of time, vibrations, or sustained/ awkward positions. This study aims to identify the most common types of CTD that may appear on office workers, and determines the main causes and symptoms of such disorders. Moreover, it will provide some practical solutions and recommendations to reduce or prevent these disorders from developing, and keep the workers away from them. Thereby enhance their productivity and provide a good opportunity for the organizations to reduce their costs and increase their profits. Moreover, the project attend to bring innovative ideas for a better understanding of the Cumulative trauma disorders (CTD)or musculoskeletal disorders (MSD) problem, which affects the employees are exposed to a large load for a long time at work, such as secretaries in universities, ministries, lawyer offices and insurance companies, and why is that issue is so persistent. It also formulates arguments to the actual prevention methods and will propose ideas about a practical tackling of the problems. Absenteeism due to injuries and diseases put a serious hypothecation on a rational development of the economic and socioeconomic systems, because of the importance of the direct and indirect costs which affects the strategies of new investments, planning and employment strategies. Subsequently any negative phenomenon in the actual economic crisis should be avoided or prevented. A questionnaire is designed to determine chronic occupational diseases that affect the office workers in Palestine. In order to identify the potential mechanism for dealing with these cases and to design an effective system to prevent them. Minitab and SPSS programs were used to analyze the collected data. The prevalence of cumulative trauma disorders among office workers determined so that 64% of office workers complain from at least one type of CTD. Moreover, the greatest incidence rate was at the foot, lower back and knee limb, while the smallest incidence rate appeared on the arm and night limb. In addition, several recommendations have been provided in terms of both engineering and administration point view.